2021
DOI: 10.4240/wjgs.v13.i7.678
|View full text |Cite
|
Sign up to set email alerts
|

Gastrectomy impact on the gut microbiome in patients with gastric cancer: A comprehensive review

Abstract: Gastric cancer is one of the most common malignancies worldwide and gastrectomy remains the only potentially curative treatment option for this disease. However, the surgery leads to significant physiological and anatomical changes in the gastrointestinal (GI) tract including loss of the gastric barrier, an increase in oxygenation levels in the distal gut, and biliary diversion after gastrectomy. These changes in the GI tract influence the composition of the gut microbiome and thus, host health. Gastrectomy-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…Elaine et al showed that the metabolism and microbial composition of gastric cancer patients were significantly altered after Roux-en-Y gastric bypass (RYGB) surgery [ 45 ]. Consistently, Vaidota et al showed that gastric cancer surgery could affect the composition of gastric microbiota [ 46 ]. Liu et al found that the gastric microenvironment determined the composition and diversity of gastric microbiota rather than the stage or type of GC.…”
Section: Microbiota and Gastric Cancermentioning
confidence: 85%
See 1 more Smart Citation
“…Elaine et al showed that the metabolism and microbial composition of gastric cancer patients were significantly altered after Roux-en-Y gastric bypass (RYGB) surgery [ 45 ]. Consistently, Vaidota et al showed that gastric cancer surgery could affect the composition of gastric microbiota [ 46 ]. Liu et al found that the gastric microenvironment determined the composition and diversity of gastric microbiota rather than the stage or type of GC.…”
Section: Microbiota and Gastric Cancermentioning
confidence: 85%
“…Microbial imbalance is also an important factor responsible for cancer, described in detail in the previous paragraph. Importantly, microbial colonization of gastric cancer can be affected by the microenvironment (microbial interaction, surgical operation, stage or type of GC and so on) [ 42 46 ].…”
Section: Microbiota and Gastric Cancermentioning
confidence: 99%
“…The protection of intestinal function plays a very important role in radical gastrointestinal tumor resection. The impairment of the intestinal barrier function can increase the risk of postoperative infectious complications, multiple organ failure, and mortality, and exacerbate local and systemic inflammatory stress responses in the intestine, influence the composition of the gut microbiome (24), leading to prolonged postoperative recovery (25). In this…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer is the most common malignancies in the world. Gastrectomy is still the only potentially curative treatment for this disease [29]. Gastric cancer is as well as esophageal cancer is one of the two major causes of cancer-related deaths in the world [30].…”
Section: Gut Microbiome Dysbiosis In Various Malignanciesmentioning
confidence: 99%
“…Bacterial dysbiosis in the stomach can strengthen gastric neoplasia development via generating tumor-promoting metabolites, DNA damage, suppressing antitumor immunity, and activating oncogenic signaling pathways [35]. Dysbiosis after gastrectomy is characterized by increased microbiome consisting of typical oral cavity bacteria, characterized by increased aero-tolerant bacteria (aerobes/facultative anaerobes), and increased genera of bile acid-transforming bacteria [29]. Lower abundance of Bifidobacteriaceae was seen only in diffuse adenocarcinoma and of Oscillibacter in intestinal adenocarcinoma [36].…”
Section: Gut Microbiome Dysbiosis In Various Malignanciesmentioning
confidence: 99%